2008
DOI: 10.1002/j.2161-1912.2008.tb00067.x
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of Content and Instructional Strategies in Multicultural Counseling Courses

Abstract: the authors present a content analysis of syllabi from introductory multicultural counseling training (Mct) courses. results suggest that these courses focus on knowledge of other cultural groups, emphasize the cultural identity exploration of the student at a lower level of training, and almost completely ignore the development of skills. the study revealed that Mct frequently includes groups beyond racial and ethnic minority groups. a broad range of instructional strategies are used, with a handful being use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
81
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 120 publications
(82 citation statements)
references
References 23 publications
1
81
0
Order By: Relevance
“…Furthermore, a content analysis of multicultural counseling course syllabi from APA-accredited counseling psychology programs indicates that such courses include little, if any, emphasis on actual multicultural counseling skill development (Priester, Jackson-Bailey, Jones, Jordan, & Metz, 2004). If nothing else, then, the findings from this study clearly indicate that our participants lacked specificity of training on self-disclosure in cross-cultural counseling, a circumstance that may have important implications for their therapeutic work with culturally diverse clients.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a content analysis of multicultural counseling course syllabi from APA-accredited counseling psychology programs indicates that such courses include little, if any, emphasis on actual multicultural counseling skill development (Priester, Jackson-Bailey, Jones, Jordan, & Metz, 2004). If nothing else, then, the findings from this study clearly indicate that our participants lacked specificity of training on self-disclosure in cross-cultural counseling, a circumstance that may have important implications for their therapeutic work with culturally diverse clients.…”
Section: Discussionmentioning
confidence: 99%
“…For example, graduate training programs rely heavily on the single-course method of multicultural counseling training (Ponterotto, 1997;Ridley, Mendoza, & Kanitz, 1994), an approach that is perhaps inadequate to support the development of competency in multicultural counseling skills (Parham & Whitten, 2003). Furthermore, a content analysis of multicultural counseling course syllabi from APA-accredited counseling psychology programs indicates that such courses include little, if any, emphasis on actual multicultural counseling skill development (Priester, Jackson-Bailey, Jones, Jordan, & Metz, 2004). If nothing else, then, the findings from this study clearly indicate that our participants lacked specificity of training on self-disclosure in cross-cultural counseling, a circumstance that may have important implications for their therapeutic work with culturally diverse clients.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, a study on introductory multicultural counseling courses conducted by Priester, Jones, Jackson-Bailey, Jana-Masri, Jordan, and Metz (2008) reported that the counselors-intraining in these courses augmented their multicultural knowledge base and self-awareness competencies. On the other hand, based on minimal skill development resulting from these courses, the authors urged further research on multicultural counseling training to expand its current overemphasis on philosophical conceptualizations.…”
Section: Single Multicultural Course -Explicit Curriculum Designmentioning
confidence: 94%